Stress resilience during the coronavirus pandemic - Vinkers, Christiaan H.; van Amelsvoort, Therese; Bisson, Jonathan I.; Branchi, Igor; Cryan, John F.; Domschke, Katharina; Howes, Oliver D.; Manchia, Mirko; Pinto, Luisa; de Quervain, Dominique; Schmidt, Mathias V.; van der Wee, Nic J.A. (European neuropsychopharmacology, 2020)
The epidemic of the 2019 novel coronavirus SARS-CoV-2, causing the coronavirus disease 2019 (COVID-19) is a global public health emergency with multifaceted severe consequences for people's lives and their mental health. In this article, as members of the European College of Neuropsychopharmacology (ECNP) Resilience, we will discuss the urgent need for a focus on resilience during the current coronavirus pandemic. Resilience is pivotal to cope with stress and vital to stay in balance. We will discuss the importance of resilience at the individual and societal level, but also the implication for patients with a psychiatric condition and health care workers. We not only advocate for an increased focus on mental health during the coronavirus pandemic but also highlight the urgent need of augmenting our focus on resilience and on strategies to enhance it.